Evolving corporate social responsibility: Towards constructive corporate participation - Goddard, Trevor; Teller, D. (The International Association for Business and Society, 2006)
This paper commences a creative challenge to conventional corporate social responsibility (CSR) literature, proposing a model of constructive corporate participation (CCP). The model arises from ongoing work conducted by the Committee for Melbourne, describing the way in which unique structures such as the Committee for Melbourne allow corporations to address complex social issues alongside government and civil society for mutual betterment of business and society. An interview series with Committee members was undertaken to establish the characteristics of the Committee set against other business organizations. The paper is set in an organizational learning framework, represents work in progress, and was undertaken to enhance understanding of the role business plays in society and its function as one of many actors influencing societal health development and wellbeing.